Lipid Nanocarriers-Loaded Nanocomposite as a Suitable Platform to Release Antibacterial and Antioxidant Agents for Immediate Dental Implant Placement Restorative Treatment - Giuseppe Angellotti; Alessandro Presentato; Denise Murgia; Giulia Di Prima; Fabio D'Agostino; Amalia Giulia Scarpaci; Maria Cristina D'Oca; Rosa Alduina; Giuseppina Campisi; Viviana De Caro (MDPI AG, 2021)
Immediate implant placement is a single-stage restorative approach for missing teeth widely used to overcome the ridge remodeling process occurring after dental extractions. The success of this procedure relies on opportune osseointegration in the surrounding tissues. To support this process, a multifunctional nanocomposite, to be applied in the fresh post-extraction socket, was here designed, prepared, and characterized. This formulation consists of quercetin (QRC)-loaded nanostructured lipid carriers (NLCs) entrapped in a chitosan-based solid matrix containing ciprofloxacin (CPX). QRC-NLCs were prepared by homogenization followed by high-frequency sonication, and thereafter this dispersion was trapped in a chitosan-based CPX-loaded gel, obtaining the nanocomposite powder (BioQ-CPX) by lyophilization. BioQ-CPX displayed desirable properties such as high porosity (94.1 ± 0.5%), drug amounts (2.1% QRC and 3.5% CPX). and low swelling index (100%). Moreover, the mechanism of drug release from BioQ-CPX and their ability to be accumulated in the target tissue were in vitro and ex vivo elucidated, also by applying mathematical models. When trapped into the nanocomposite, QRC stressed under UV light exposure (50 W) was shown to maintain its antioxidant power, and CPX and QRC under natural light were stable over nine months. Finally, both the measured antioxidant power and the antimicrobial and antibiofilm properties on Staphylococcus aureus demonstrated that BioQ-CPX could be a promising platform to support the single-stage dental restorative treatment.